Characteristics and reasons for light rain reduction in Southwest China in recent decades. (October 2019) - Zhang, Shuang; Wu, Jian; Zhao, Deming; Xia, Lan
Although light rain events have a small intensity and amount, light rain also exerts a significant influence on the environment and climate, and observations have revealed a significant reduction in light rain in many regions around the globe. The specific reasons for light rain reduction have not been clearly revealed. Some studies attribute the reduction in light rain to an increase in aerosol, while other studies tend to associate it with global warming. Therefore, further studies should be conducted to increase knowledge regarding the reasons for the decrease in light rain. Light rain events were analyzed using daily precipitation data collected from 67 gauge stations across Southwest China from 1960 to 2010. The results show that both the amount of light rain and the number of light rain days have decreased during the last 50 years at different magnitudes (0–2 mm, 2–5 mm, and 5–10 mm), in which the light rain amount and number of light rain days for 0–2 mm of rainfall present the largest regionally averaged decreasing rates of –0.20 mm/a and –0.73 days/a from 1960 to 2010, respectively. Furthermore, the maximum (minimum) light rain amount and number of light rain days appear in summer (winter). In addition, an increasing trend in the light rain amount in discrete events and a decreasing trend in the light rain amount in consecutive events are simultaneously revealed, in which the reduction in the frequency of consecutive light rain events is more significant than that of discrete light rain events. The reduction in light rain in the eastern part of Southwest China from 1979 to 2010 is mainly caused by a combination of water vapor reduction and warming. Moreover, the influence of aerosols on the observed reduction in light rain is not statistically significant at the inter-annual scale. The results provide some main correlation factors for predicting the long-term changes of light rain in China and even the global region.